D-Days in the Pacific : the path to victory from Guadalcanal to Okinawa ([Burlington, VT] : A&E Home Video ; New York : Distributed by New Video, 2005)
Though most people associate D-Day with the massive invasion of Normandy on June 6, 1944, few are aware that 'D-Day' is actually military code for any amphibious operation. Take a look at dozens of the more than one hundred D-Days waged in the Pacific. The ultimate guide to the epic campaign orchestrated by American forces in the Pacific, this two volume set includes seven documentary features.
Death at the tideline -- Closing the jaws -- The final graveyard -- The bloody hills of Peleliu -- Biography: Admiral Chester Nimitz -- Biography: General Douglas MacArthur.
Documentary.
Title from container.
DVD, region 1; Dolby Digital, stereo.
Keywords: Nimitz, Chester W. -- 1885-1966.; MacArthur, Douglas, -- 1880-1964.; World War, 1939-1945 -- Campaigns -- Pacific Ocean; World War, 1939-1945 -- Amphibious operations; World War, 1939-1945 -- Campaigns -- Japan -- Okinawa Island